The role of task meaning on output in groups: Experimental evidence. (27th July 2017) - Bäker, Agnes; Mechtel, Mario
Abstract : Previous research has shown a detrimental effect of low task meaning on individual work output. This paper analyzes whether peer settings are able to counteract this negative effect of low task meaning. First, our results confirm that a low level of task meaning decreases individual output when working alone. However, this effect vanishes completely when working in the presence of a peer. Our analysis implies that organizing work in peer settings might be particularly beneficial in work environments with a low level of task meaning.